Pola Asuh Guru Dan Orang Tua Kala Pandemi: Model Penerapan Dan Problematika Yang Dihadapi - Noer Rohmah; Zaenal Fanani (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Online learning, which was one of the government's policies in addressing the past Covid-19 pandemic, turned out to have created many problems. This problem is experienced by parents and teachers, especially in applying appropriate parenting so that learning remains effective when learning conditions cannot be carried out normally due to the pandemic situation. This study aims to explore the model, the problems encountered, along with the solutions carried out, especially in terms of parenting that must be adjusted. The approach used in this research is qualitative by designing case studies. The research results show that; 1) the parenting models used include: democracy (majority), permissive and authoritarian. 2) Some of the forms of parenting problems faced by teachers and parents include: there are teachers who are still weak in using digital literacy, including those who are still weak in using various learning models and strategies; character and knowledge of parents related to limited educational materials; busy parents. 3) Various steps have been taken by the school in overcoming these problems, both problems from teachers and parents so that learning that is carried out boldly can remain effective and enjoyable.